Reflexive religion : the new age in Brazil and beyond - D'Andrea, Anthony, (Religion in the Americas, 2018)
Reflexive Religion: The New Age in Brazil and Beyond examines the rise of alternative spiritualities in contemporary Brazil. Masterfully combining late modern theory with multi-site ethnographies of the New Age, it explains how traditional religion is being transformed by processes of reflexivity, globalization and individualism. The book unveils how the New Age has entered Brazil, was adapted to local Catholic, Spiritist and psychology cultures, and more recently how the Brazilian Nova Era re-enters transnational circuits of spiritual practice. It closely examines Paulo Coelho (spiritualist novels), Projectiology (astral projection) and Santo Daime (neo-shamanism) to understand the broader "new agerization" of Christianity and Spiritualism. Reflexive Religion offers a compelling account of how the religious field is being updated under late modern conditions.